Ubiquitination of the PI3-kinase VPS-34 promotes VPS-34 stability and phagosome maturation - Liu, Jinchao (J Cell Biol, 2018)
Apoptotic cells generated by programmed cell death are engulfed by phagocytes and enclosed within membrane-bound phagosomes. Maturation of apoptotic cell–containing phagosomes leads to formation of phagolysosomes where cell corpses are degraded. The class III phosphatidylinositol 3-kinase (PI3-kinase) VPS-34 coordinates with PIKI-1, a class II PI3-kinase, to produce PtdIns3P on phagosomes, thus promoting phagosome closure and maturation. Here, we identified UBC-13, an E2 ubiquitin–conjugating enzyme that functions in the same pathway with VPS-34 but in parallel to PIKI-1 to regulate PtdIns3P generation on phagosomes. Loss of ubc-13 affects early steps of phagosome maturation, causing accumulation of cell corpses. We found that UBC-13 functions with UEV-1, a noncatalytic E2 variant, and CHN-1, a U-box–containing E3 ubiquitin ligase, to catalyze K63-linked poly-ubiquitination on VPS-34 both in vitro and in Caenorhabditis elegans. Loss of ubc-13, uev-1, or chn-1 disrupts ubiquitin modification of VPS-34 and causes significantly reduced VPS-34 protein levels. Our data suggest that K63-linked ubiquitin modification serves as a general mechanism to modulate VPS-34 stability in multiple processes.